Potensi Asap Cair Sebagai Antioksidan Terhadap Ketengikan Minyak Goreng Pabrikan Yang Aman Bagi Masyarakat - Wonga, Maria Yolanda; Umbu, Yohanis (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
Cooking oil is one of the important needs of the community in meeting their daily needs. The use of repeated cooking oil manufacturers with high heating can lead to oxidation of oil which can cause the composition of the oil to change and produce compounds that have a rancid odor. This study aims to determine the effect of adding liquid smoke to the rancidity of the manufacturer's cooking oil with the most effective volume based on the storage time. Liquid smoke from rice husk is obtained from the pyrolysis process of rice husk which contains components of cellusosa, hemicellulose and lignin which produce phenol compounds, acid compounds and derivatives, which can be used as antioxidants to prevent rancidity in the manufacturer's cooking oil. The parameters used in the analysis of the quality of the manufacturer's cooking oil are the test of the levels of free fatty acids, acid numbers, and peroxide numbers. The results showed that the higher the volume of liquid smoke added, the smaller the increase in levels of free fatty acids, acid numbers and peroxide numbers, the most effective volume of liquid smoke was 27 ml at 1 week storage time